The role of energy service contracting in delivering energy efficiency measures for local authorities in the UK - Nolden, C (European Council for an Energy Efficient Economy, 2015)
Energy service contracting is a niche activity in the UK, encompassing a variety of approaches that allow organisations to tap into underexploited energy efficiency, cogeneration and increasingly also renewable energy generation potentials. It involves outsourcing of one or more energy generation, conversion or management process(es) by sharing, spreading and/or transferring risk, which may involve funding investments through savings in energy costs. The last point is of particular relevance to local authorities in the UK as tightening budgets resulting from austerity measures imply that both investment backlogs and the need to comply with carbon reduction commitments are rarely addressed.